Adoption of Post-Harvest Handling Practices by Ginger Farmers in Palpa District, Nepal - Poudel Chhetri , Bidhya; K.C., Suraj; Ghimire , Sudip (Newinera Publisher, 2022)
Ginger has the potential for export and increased income for farmers in Nepal. Proper post-harvest handling practices has led to low market prices and significant post-harvest losses of ginger. The study was conducted in Palpa district to examine the post-harvest practices and technology adoption among ginger farmers. Data from 66 farmers in Bagnashkali, Purbakhola, Nisdi, and Rampur municipalities was collected through interviews, key informant interviews, and focus group discussions. Descriptive analysis was performed using MS Excel and SPSS. Results showed that 72.7% of farmers practiced storage, with Bhakari (60.41%) and Pit (39.59%) being the common storage types. Storage molds affected 72.2% of respondents, while 28.8% reported wrinkling during storage. Washing was practiced by only 7.6% of farmers. Manual grading was reported by all respondents, with no commercial grading observed. Black sutho production was carried out by 65.2% of farmers. Value addition activities such as sorting were practiced by 65% of respondents, while 25% engaged in transportation and packaging. Respondents' awareness of ginger post-harvest practices varied, with 75.76% having low awareness, 16.66% medium awareness, and 7.58% high awareness. Farmers' general precautions during harvesting, such as avoiding rhizome injury and minimal trimming and sorting, were not accompanied by specific precautionary practices, contributing to their challenges. The findings emphasize the importance of adopting modern post-harvest practices to increase production, improve product quality, and command higher market prices. Implementing these measures will enable ginger farmers in Palpa district to enhance their income and contribute to the growth of the ginger industry in Nepal.